The Effect of AI Technology, Innovation Readiness, and Digital Entrepreneurship on Competitive Advantage in Start Up in Jakarta - Bakri Bakri; Ajub Ajulian ZM; Siska Yulia Defitri; Halek Mu'min (Westscience Press, 2024)
This study investigates the impact of AI technology adoption, innovation readiness, and digital entrepreneurship on competitive advantage in startup enterprises within Jakarta's entrepreneurial ecosystem. A quantitative approach employing Structural Equation Modeling (SEM) with Partial Least Squares (PLS) analysis was utilized to analyze data collected from 229 startup founders and executives. The findings reveal significant positive relationships between AI technology adoption, innovation readiness, digital entrepreneurship, and competitive advantage. Specifically, startups that strategically embrace AI technologies, foster innovation readiness, and leverage digital entrepreneurship practices demonstrate higher levels of competitive advantage. The study contributes to theoretical understanding by extending literature on technology-driven entrepreneurship and provides practical insights for startup stakeholders and policymakers aiming to enhance the competitiveness of Jakarta's startup ecosystem.